Synthesis of Some New Amino Carbonyl Compounds by Mannich Reaction - Dawood, Nagham; Saeed, Banan; Saeed, Zainab (Molekul, 2024)
Beta-aminocarbonyl compounds are important intermediates produced from Mannich condensation. In this research, benzaldehyde, para-hydroxy acetophenone or para-nitro acetophenone were reacted with a various of primary aromatic amines to give compounds (1-7) and (8-14), respectively. The chemical formulas of the synthesized compounds were confirmed by conducting some physical and spectroscopic measurements, such as, melting points, IR and H1-NMR spectrum. After testing the biological activity of some of the synthesized compounds (8,10,11,13) using Gram-positive (Streptococcus, and Staphylococcus aureus), Gram-negative (Klebsiella spp., and Escherichia coli) bacteria, as well as yeast strains, were chosen for this investigation (candidan albicans). Isolated bacteria were identified using standard methods of isolation and identification, including direct assays and culture on various media. Some theoretical tests have also been carried out such as SwissADME and cardioToxCSM prediction on all prepared compounds to predict their activity in terms of pharmacokinetic properties (ADME) and also predict their cardiotoxicity on some heart functions such as arrhythmia, cardiac failure, heart block, hERG toxicity, Hypertension (HT), and Myocardial Infarction (MI). Keywords: Secondary amines, aldehyde, Mannich condensation, antimicrobial activity.